Effect of spray-dried blood meal in the phase III diet - Kats, L.J.; Friesen, K.G.; Richert, B.T.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 216 weanling pigs was used to evaluate the use of spray-dried blood meal (SDBM) in the phase III diet for pigs weighing approximately 25 pounds. At weaning, pigs (initially 11.6 lb and 21 d of age) were allotted by weight, gender, and ancestry to the dietary treatments. There were six pigs per pen with six replications per treatment. Pigs were started on a common phase I diet containing 20% dried whey, 7.5% spray-dried porcine plasma, and 1.75% spray-dried blood meal. This diet was formulated to contain 1.5% lysine and .44% methionine. On d 7 postweaning all pigs were switched to a common phase II diet that contained 10% dried whey and 2.5% spray-dried blood meal and was formulated to contain 1.25% lysine and .35% methionine. On d 21 postweaning and when weight averaged approximately 25 pounds, pigs were switched to one of six diets, control or containing .5, 1.0, 1.5, 2.0, or 2.5% spray-dried blood meal, that were formulated to contain 1.15% lysine. Pigs were fed experimental diets from d 21 to 42 postweaning (phase III). During phase I, average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G) were .54 lb, .61 lb, and 1.16, respectively. During phase II, ADG, ADFI, and F/G were .62 lb, 1.15 lb, and 1.90, respectively. On d 21, pigs weighed an average of 24 pounds when they were switched to the experimental diets. During phase III, linear (P < .05) depressions in ADG and F/G occurred with the addition of increasing levels of spray-dried blood meal in the diet. However, the reduction in performance was only evident at the 2 and 2.5% blood meal levels. Lower blood meal additions to the diet (< 2%) had no influence on pig performance. Similar to earlier research, our results indicate that complex protein sources are not required in the phase III diet for optimal pig performance.
Keywords: Swine; Blood meal; Starter pigs; Performance